Development Level Evaluation of Tax Governance Digitalization Using Quadripartitioned Single-Valued Neutrosophic Sets - Shuguang Wang; Renjie Bao (Neutrosophic Sets and Systems)
A key component of improving the accountability, efficiency, and openness of public financial institutions is the digital transformation of tax governance. Assessing the degree of development of digital tax governance has become crucial for institutions and policymakers due to the increasing needs for safe data management, sophisticated audit systems, and real-time compliance on a worldwide scale. Using a neutrosophic set evaluation methodology, this study suggests a thorough framework for determining the level of digitalization maturity in tax governance. Six digital governance options are evaluated using eight fundamental criteria, which range from regulatory preparedness to automation, cybersecurity, and AI integration. The study finds important development trends, digitalization gaps, and performance standards among governance models by combining expert opinion with methodical comparative methodologies. This study uses the neutrosophic set to solve uncertainty problems. We use Quadripartitioned Single-Valued Neutrosophic Sets framework to rank the alternatives.